A systems-oriented analysis of the grapevine R2R3-MYB transcription factor family uncovers new insights into the regulation of stilbene accumulation - Wong, Darren Chern Jan; Höll, Janine (DNA research, 2016)
R2R3-MYB transcription factors (TFs) belong to a large and functionally diverse protein superfamily in plants. In this study, we explore the evolution and function of this family in grapevine (Vitis vinifera L.), a high-value fruit crop. We identified and manually curated 134 genes using RNA-Seq data, and named them systematically according to the Super-Nomenclature Committee. We identified novel genes, splicing variants and grapevine/woody-specific duplicated subgroups, suggesting possible neo- and sub-functionalization events. Regulatory network analysis ascribed biological functions to uncharacterized genes and validated those of known genes (e.g. secondary cell wall biogenesis and flavonoid biosynthesis). A comprehensive analysis of different MYB binding motifs in the promoters of co-expressed genes predicted grape R2R3-MYB binding preferences and supported evidence for putative downstream targets. Enrichment of cis-regulatory motifs for diverse TFs reinforced the notion of transcriptional coordination and interaction between MYBs and other regulators. Analysis of the network of Subgroup 2 showed that the resveratrol-related VviMYB14 and VviMYB15 share common co-expressed STILBENE SYNTHASE genes with the uncharacterized VviMYB13. These regulators have distinct expression patterns within organs and in response to biotic and abiotic stresses, suggesting a pivotal role of VviMYB13 in regulating stilbene accumulation in vegetative tissues and under biotic stress conditions.
Gesehen am 16.08.2021